Aplikasi Elemen Pemikiran Saintifik Dalam Pengajian Syariah - Azhar, Alias; Abdul Rahim, Rahimin Affandi (Jurnal Fiqh, 2010)
Perspective that considers the full value of knowledge is a kind of knowledge constructed by the human mind in the context of culture, education and social conception. In principle, the development of a strong education system requires the development of educational curricula and teaching and learning environment that meets the current needs. One of the important elements that should be included in that system is the application of scientific thinking. In the field of Shariah studies, this will be the catalyst for the birth of the knowledge that generates an optimal mind function. It will produce students who can think rationally, carefully and objectively which provide them a force of formula and analysis, so as to enhance the ability of ijtihad.